The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/molecules24112133
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Review on the Extraction, Antioxidant Content and Antioxidant Potential of Different Parts of Walnut (Juglans regia L.) Fruit and Tree

Abstract: As a valuable tree nut, walnut is a well-known member of the Juglandaceae family. The fruit is made up of an outer green shell cover or husk, the middle shell which must be cracked to release the kernel, a thin layer known as skin or the seed coat, and finally, the kernel or meat. The nutritional importance of walnut fruit is ascribed to its kernel. The shell and husk are burned as fuel or discarded away as waste products. In the past two decades, the evaluation of the phenolic content and antioxidant activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 182 publications
2
89
0
4
Order By: Relevance
“…Walnut (Juglans regia L.) is considered a priority plant by the food and agriculture organization (FAO) and is a strategic species for human nutrition [8]. Walnut co/by-products, rich in phenolic compounds, are produced in agricultural industries and are a valuable source of antioxidants for animal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Walnut (Juglans regia L.) is considered a priority plant by the food and agriculture organization (FAO) and is a strategic species for human nutrition [8]. Walnut co/by-products, rich in phenolic compounds, are produced in agricultural industries and are a valuable source of antioxidants for animal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the antioxidant activity of DPPH was more efficient with methanol than with ethanol. This antioxidant activity was 70% with methanol compared to 33% with ethanol knowing that methanol is more polar than ethanol and can extract more chemicals [ 18 ]. This was also observed by the transformation of violet color to yellow color as the concentration of DPPH was increased from 0.1 to 0.5 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Recent investigations of these by-products demonstrated that they contain valuable compounds including phenolics. 6,[28][29][30] The green husk of the walnut fruit is available in high amounts. Recently, Oliveira, et al 31 recognized the aqueous extract of the low-cost green husk as an excellent natural source of phenolic compounds with antimicrobial and antiradical activities.…”
Section: Walnutsmentioning
confidence: 99%
“…This part of the walnut fruit has not been comprehensively studied in comparison with those of other tree nuts. 30 The most critical and divergent antioxidants are concentrated in this part of the fruit and act as protective agents against harmful UV radiation effects, as well as microbial, fungal, and viral contamination.…”
Section: Walnut Fruitmentioning
confidence: 99%
See 1 more Smart Citation